Effect of surface chemistry of Fe-Ni nanoparticles on mechanistic pathways of azo dye degradation - Bokare, Alok D.; Chikate, Rajeev C.; Rode, Chandrashekhar V.; Paknikar, Kishore M. (Environmental Science & Technology, 2007)
The degradation of Orange G a monoazo dye, in aqueous solutions was investigated using as-synthesized and stored Fe-Ni bimetallic nanoparticles. Batch experiments with a nanocatalyst loading of 3 g/L showed complete. dye degradation (150 mg/L) after 10 min of reactiontime. HPLC-MS analysis of the degradation products showed that assynthesized nanoparticles reductively cleaved the azo linkage to produce aniline as the major degradation product. However, 1-year-stored nanoparticles showed an oxidative degradation of Orange G through a hydroxyl-radical induced coupling of parent and/or product molecules. XPS analysis in corroboration with HPLC-MS data showed that the surface chemistry between Fe and Ni in assynthesized and stored nanoparticles play a crucial role. in directing the mode of degradation. Reductive dye degradation using as-synthesized nanoparticles proceeded through hydride transfer from nickel, whereas formation of a Fe (2+) -Ni(0) galvanic cell in stored nanoparticles generated hydroxyl radicals from water in a nonFenton type reaction. The latter were responsible for the generation of radical centers on the dye molecule, which led to a coupling-mediated oxidative degradation of Orange G. The generation of hydroxyl radicals is further substantiated with radical quenching experiments using ascorbic acid indicating that stored nanoparticles degrade Orange G through a predominantly oxidative mechanism. HPLC-MS and XPS analysis of dye degradation using as-synthesized nanoparticles exposed to air and water confirmed that the reductive or oxidative degradation capability of Fe-Ni nanoparticles is decided by the time and type of catalyst aging process.